Rooting of stem cuttings with different indole 3 butyric acid (IBA) treatments and development of micropropagation protocol for Piper betle L. node culture - Muttaleb, Qusay Abdulhamza; Abdullah, Thohirah Lee; Rashid, Azmi Abdul; Hassan, Siti Aishah (Scientific Research Publishing, 2017)
The present study, conducted during 2016 and 2017 seasons, aimed to investigate the effect of IBA on rooting of Piper betle L. stem cuttings (softwood and semi-hardwood). The experiment was undertaken in misting house field 2 UPM using the sand media to determine the adventitious roots initiation and development using the histological method. The cuttings were treated with different IBA concentrations (0, 500, 1000, 1500 and 2000 mg/L). The nodes explants were used in the development of a protocol for in vitro propagation of P. betle L., with different concentrations of Clorox with different times of immersion (20% Clorox 10 minutes, 30% Clorox 10 minutes, 20% Clorox 20 minutes, and 30% 20 minutes). In multiplication of the plantlets, Murashige and Skoog (MS) medium with different concentrations of BAP (0, 0.5, 1.0, 2.0 mg/L) were used to investigate the rooting of the explants. The results indicated that the types of the cuttings were different in the rooting capacity and the length of the roots. Moreover, it was found that in comparison with the control treatment, by a rise in the concentrations of the IBA, there was a significant upsurge in the rooting percentage, the root diameter, and the number of the roots. The results indicated that the types of cutting with 1000, 1500 and 2000 mg/L IBA perform better in the root percentage (100%) in the semi hardwood cuttings. The best results, however, were 2000 mg/L IBA in the semi hardwood cuttings, with the number of the roots to be 35.05, and the fresh weight of the roots to be 3.94 g, the dry weight of the roots to be 0.33 g, the length of the roots to be 391.88 cm, the roots diameter to be 1.21 mm, the surface area of the roots to be 121.83 cm2, and the root volume to be 2.99 cm3. Nonetheless, the optimal concentration of Clorox with the time immersion was 20% with the 20-minute immersion time, which produced a shoot induction percentage of 30% dead explants and a mean number of 70.00 shoots per explant and the optimal concentration of benzylaminopurine (BAP) at 1.0 mg/L. It is of note that a shoot induction percentage of 22.29% and a mean number of 4.1% number of auxiliary bud per treatment. P. betle shoots in MS medium without PGR MS (0.0) yielded a good rooting.